Blog Credibility: Examining the Influence of Author Information and Blog Reach. - Borah, Porismita (Atlantic Journal of Communication)
Literature on blog credibility shows that blog readers find blogs more credible than the mainstream media, whereas it is just the opposite with the general audience. Using three experiments, the present study examines the influence of two factors: identity of the blogger (journalist blogger vs. nonjournalist blogger) and reach of the blog (low vs. high) on blog credibility. Findings show that in the case of the general audience, the journalist blogger was perceived as more credible. Of interest, results also show that reach of the blog-influenced blog credibility only in the case of the nonjournalist blogger. Implications are discussed.